Exploring the feasibility and acceptability of Continuous Glucose Monitoring among people with type 1 diabetes and healthcare providers in South Africa’s public sector: A qualitative study - Lorrein Muhwava; Elena Marbán-Castro; Mpho Silima; Maria Karsas; Tanja Kemp; Johane Freitas; Yvonne Kamau; Beatrice Vetter; Cathy Haldane; Paul Rheeder; Michelle Carrihill; Joel A. Dave; et al. (PLoS ONE, 2026)
Background Continuous Glucose Monitoring (CGM) is an advancement in diabetes management, offering real-time insights into blood glucose levels and facilitating decision-making around diabetes care. However, its adoption in low- and middle-income countries (LMICs) remains low. This study explored the perceptions and experiences of CGM use among people living with type 1 diabetes (T1D), their caregivers, and healthcare providers (HCPs) in the public sector in South Africa. Methods Convenience sampling was used to recruit participants from the ACCEDE study – a pragmatic randomised controlled trial on CGM use among people living with T1D in South Africa. Between July 2024 and February 2025, we conducted focus group discussions (FGDs) with recipients of care and caregivers and semi-structured interviews (SSIs) with HCPs across study sites in Cape Town and Pretoria. All FGDs and SSIs were audio-recorded, transcribed, and analysed using MAXQDA 2022. Data analysis followed thematic content analysis, and the findings presented according to the socioecological framework. Results A total of 107 participants, including 75 people living with T1D, 17 caregivers, and 15 HCPs, were included in the study. CGM was generally perceived as acceptable due to convenience, reduced need for finger-prick testing, and enhanced understanding of glucose patterns. Feasibility was enhanced by ease of use, access to training, and social support. Key barriers included cost, limited awareness, and socio-economic constraints such as food insecurity and lack of access to transport. Conclusion CGMs are both feasible and acceptable within South Africa’s public healthcare context. However, integration requires a coordinated, multi-level response, strengthening provider and patient awareness, knowledge, adequately resourced multi-disciplinary diabetes care teams, and addressing affordability through supportive health policies.